Electrical and barrier properties of modified polyaniline coating films and its effects on the corrosion protection of mild steel / Amirah Amalina Ahmad Tarmizi - Ahmad Tarmizi, Amirah Amalina (Institute of Graduate Studies, 2017)
The study investigated the coating properties of polyaniline (PANI), polyaniline with nano silica (PANI nSi) and polyaniline with 3-amino silane modified nano silica (PANI 3-APS modified nano silica). Investigation were carried out on the effects of nano silica and amino-silane modified nano silica fillers on the structure, morphology and its influence on the electrical and ionic barrier properties of polyaniline. Fourier Transform Infrared (FTIR) showed the successful formation of PANI, PANI nSi and PANI 3-APS modified nano silica. Correlation between concentration of acid and fillers weight ratio with conductivity were studied. The electrical conductivity of all samples was determined using the bulk resistance value obtained from the Nyquist plot in the frequency range of 0.1 Hz to 100 MHz. PANI prepared in 0.1 M oxalic acid shows the highest room temperature electrical conductivity value of, 2.52 x 10-6 S cm-1. The highest electrical conductivity of PANI nSi was 2.4 x10-4 S cm-1 for PANI containing 20%w/w nano silica fillers. For PANI 3-APS modified nano silica, PANI added with 20%w/w of 3-APS modified nano silica fillers exhibit the highest conductivity values which were 4.0 x10-6 S cm-1. PANI, PANI nSi and PANI 3-APS modified nano silica with the optimum condition was selected for further characterization. The study also calculated the conductivity of all selected samples in wet condition. The transference numbers determined the conductivity behaviour of all chosen samples in dry and wet conditions. The transference numbers were calculated using Wagner’s polarization method...